Towards Biocatalytic Oxidation of Secondary Alcohols to Carbonyl Products of Relevance for Flavors and Fragrances - Puchľová, Eva; Hilberath, Thomas; Vranková, Kvetoslava; Hollmann, Frank (Frontiers in Catalysis, 2022)
Non-enantioselective alcohol dehydrogenases (ADHs) are rarely found in the biocatalysis portfolio. Generally, highly enantioselective ADHs for the reduction of prochiral ketones are sought for. Such enzymes, however, are not suitable if the complete oxidation of racemic secondary alcohols is desired. In the current contribution we report the ADH from Sphingobium yanoikuyae (SyADH) as non-enantioselective ADH for the complete oxidation or rac-2-heptanol (representing further 2-alcoanols).